Synthesis of mixed oligodeoxyribonucleotides following the solid phase method. - Elmblad, A (1982)
A method for the synthesis of mixed dimers, trimers and oligonucleotides on a solid support using monomeric protected nucleoside phosphochloridites (1a-d) has been developed and the different nucleoside reagents, and the results show that yields of different oligomers in a mixture could be directly correlated to the concentration of the four reagents. Separation of mixed oligomers on a reversed phase C18 column has also been studied.